BAMBOO CRAFT SMALL BUSINESS EMPOWERMENT IN KERTAWANGI VILLAGE, CISARUA DISTRICT, WEST BANDUNG DISTRICT - Siti Patimah; Erti Dinihayati (Pasundan International of Community Services Journal (PICS-J), 2022)
One of the natural resources in West Bandung Regency is bamboo. The products produced vary, mostly in the form of household appliances. The problems faced by business actors are related to marketing their products. In addition, it is also related to production, where there are many orders but are constrained by equipment, especially machines. In addition, business actors do not know how much profit or loss they experience each month because there is no bookkeeping done. The implementation method used to overcome the problems faced by business actors is through training and technical guidance. The training is carried out by giving lectures and understanding related to marketing and finance. The technical guidance carried out is by direct practice and continued by providing understanding until finally being able to be independent. In addition, the provision of machines to partners. Training activities and marketing guidance have been carried out in the form of making online marketing features on social media, namely Facebook and Instagram. As well as the provision of machines to be able to draw quickly, accurately, cheaply and neatly. In addition, training and simple financial texts have also been provided. So that partners can make simple records and can determine the determination of the cost of production.